2008
DOI: 10.1007/s11390-008-9155-6
|View full text |Cite
|
Sign up to set email alerts
|

Query Performance Prediction for Information Retrieval Based on Covering Topic Score

Abstract: We present a statistical method called Covering Topic Score (CTS) to predict query performance for information retrieval. Estimation is based on how well the topic of a user's query is covered by documents retrieved from a certain retrieval system. Our approach is conceptually simple and intuitive, and can be easily extended to incorporate features beyond bagof-words such as phrases and proximity of terms. Experiments demonstrate that CTS significantly correlates with query performance in a variety of TREC tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…poor quality. The work by Lang et al [96] is also similar in spirit. Here, each query term is considered as a separate concept and the more concepts are covered in the result list, the better the estimated result quality.…”
Section: Results List Analysismentioning
confidence: 69%
“…poor quality. The work by Lang et al [96] is also similar in spirit. Here, each query term is considered as a separate concept and the more concepts are covered in the result list, the better the estimated result quality.…”
Section: Results List Analysismentioning
confidence: 69%
“…Hao Lang et al [11] evaluate query performance based on the covering topic score that measures how well the topic of the query is covered by documents retrieved by the system (dynamic prediction). Cronen-Townsend et al [3] propose to predict query performance by computing the relative entropy (clarity score) between a query language model and the corresponding collection language model (static prediction).…”
Section: Related Workmentioning
confidence: 99%
“…The WIG (weighted information gain) predictor, developed in that work, effectively measures the difference between the score of the K top-ranked documents and the average document returned in response to a query. Others [Lang et al 2008] have shown that the performance of a ranked list is correlated to the ability of the top-ranked documents to cover all aspects of a query. Some relevant work [Vinay et al 2008] investigates different document score normalisation techniques and aims to estimate query performance based on the these normalised scores.…”
Section: Query Performance Predictionmentioning
confidence: 99%